Putting Your Knowledge Out There - Ekart, Donna F. (My University, 2009)
How to get the information you publish elsewhere to the places your users are looking by using RSS feeds and a few simple tools to customize library computer desktops.
Keywords: Libraries; RSS; Blogs; Feed readers; Technology; Desktop